Penerapan Model Pembelajaran Agama Islam bagi Anak Berkebutuhan Khusus di Sekolah Dasar Kota Samarinda - Hermawati, Hermawati (SYAMIL: Journal of Islamic Education, 2016)
Actually the child with special needed is a child that has privileges. At inclusive school, children with special needed are mingled with normal children in a school. Here, the children with special needed and normal children are treated equally. Based on the fact, the researcher is interested to conduct a research about the uniqueness of the child with special needed, especially about Islamic teaching model for the child with special needed in one of state school of elementary school in Samarinda. Because not all teachers can apply the model. Sometimes, they find difficulties in choosing the appropriate model in teaching them because there are some children those who have different characteristics. The objective of this research is to identify Islamic teaching model for the child with special needed at SD Negeri 016 District Sungai Kunjang Samarinda City is assigned as inclusive school. The design of this research is qualitative. The data analysis of the study is descriptive qualitative, where it is conducted with a natural setting. The focus of the research is to find the concept in application of Islamic teaching model for the child with special needed at SD Negeri 016 District Sungai Kunjang Samarinda City. The subject of the research is Islamic Education teachers and students (the children with special needed) are as informant. The instruments of the research are interview guide, observation sheet and documentation.The result of the research is in designing program, hopefully must be oriented and can define the strategy and appropriate model that can be applied to the children with special needed. Based on the data display above, it is showed that Islamic teaching model that used in teaching is very simple, they do not use electronic devices/technology, they only use pictures are made by teacher, puzzle, story repetition model, and demonstration. Instructional media, infrastructure is not complete. The evaluation must be repeated until reach KKM is determined. Obstacles are faced is very different from normal children, because obstacles that is faced is suitable with the children with special needed, namely mental obstacle of each student. While obstacle is faced by Islamic education teachers is lack of instructional media, infrastructure and supervision.